PENGARUH PROMOSI, KEMUDAHAN, DAN KEGUNAAN TERHADAP KEPUTUSAN PENGGUNAAN DOMPET DIGITAL SHOPEEPAY PADA MAHASISWA JURUSAN MANAJEMEN BISNIS SYARIAH ANGKATAN 2018 - Umi Nadirotul Umah; Siswahyudianto Siswahyudianto (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
This research aims to analyze the influence of promotion, convenience, and usability on the decision to use shopeepay digital wallets in students majoring in Sharia Business Management Class of 2018. The approach used in this research is a quantitative research approach with a type of associative quantitative research. The data sample used in this study amounted to 100 respondents taken from students majoring in Sharia Business Management Class of 2018. The data is analyzed using instrument tests (validity tests and reliability tests), classical assumption tests (normality tests, multicollinearity tests, heterochemicity tests, multiple regression tests), hypothesis tests (partial tests (t), simultaneous tests (f), and determination coefficient analysis (R2). The results of this study showed that partial (1) promotion had a positive and significant effect on usage decisions. (2) Convenience of positive and insignificant effect on usage decisions. (3) Usability has a positive and significant effect on usage decisions. Then simultaneously it can be known that (4) promotion, convenience, and usability have a positive and significant effect together on the decision to use Shopeepay Digital Wallet in Students of the Department of Sharia Business Management Class of 2018.